Individual Differences in Sleep Quality: Exploring the Impact of Temperament on Sleep Through Anxiety and Depression - Stefano Lasaponara; Angelica Scuderi; Elisa Pellegrini; Ludovica Annarumma; Valentina Piga; Sara Lo Presti; Maurizio Gorgoni (Personality and Mental Health, 2026)
ABSTRACT According to the functional ensemble of temperament (FET) model, individual differences in temperament arise from the balance of neurotransmitter systems also crucial for regulating circadian rhythms and sleep, suggesting a strong neurobiological link between temperament and sleep behavior. The present cross‐sectional study examined whether FET‐defined temperamental traits predict interindividual variation in sleep measures. A total of 394 healthy adults completed the Structure of Temperament Questionnaire (STQ‐77) and validated measures of sleep quality, insomnia severity, daytime sleepiness, and presleep arousal, together with indices of anxiety and depression. Several temperamental traits showed robust associations with sleep outcomes. Neuroticism and impulsivity were associated with poorer sleep quality, greater insomnia severity, and heightened presleep cognitive arousal; these effects were largely mediated by anxiety and depression. Higher social tempo was associated with better sleep and reduced daytime sleepiness. Additional associations emerged for empathy, probabilistic thinking, plasticity, and physical endurance, indicating that orientation, integration, and maintenance FET systems contribute to shaping sleep behavior. These findings indicate that stable, neurochemically grounded temperamental traits may shape interindividual sleep differences, with affective distress as a central mediator. Integrating temperament models into sleep research provides a biologically coherent framework for identifying both risk and resilience factors and informs personalized sleep interventions.